STUDENTS’ PERCEPTION ON EMPLOYING SELF-DIRECTED FEEDBACK IN WRITING - Rizky Amelia (JOALL (Journal of Applied Linguistics and Literature), 2020)
The gaps in feedback implementation bring this study to unravel students’ perception on employing self-directed feedback in writing. As the results of the previous studies on this concern are non-comparable, this study aims is to unravel students’ perception on employing self-directed feedback in writing. Employing a descriptive qualitative design, this study involved 23 English Department students of FKIP Universitas Lambung Mangkurat. The results show that students perceive self-directed feedback positively. It is seen from the correction that they make after the implementation of the self-directed feedback. However, students’ reflection on the use of self-directed feedback shows various perceptions. Therefore, teacher can wisely design which feedback given to whom. The students who are able to provide self-directed feedback can achieve maximum result of learning, and teacher can focus to assist the other students who need teacher feedback during the writing process. It is suggested to further researchers to investigate students’ emotional responses during the feedback in writing process or to investigate other factors that influence feedback.